How stressful life events and violence are related to mental health: the protective role of social relations in African context - Nyarko, Felix; Peltonen, Kirsi; Kangaslampi, Samuli; Punamaki-Gitai, Raija-Leena (Elsevier, 2026)
Adolescents are universally expected to be at risk for heightened stress and violence, and subsequently to mental health problems. Good social relationships may protect their mental health, but research has mainly focused on singular relations, such as peer popularity or general social support. The current study analyses the buffering role of multiple relationships in an African context. First, how stressful life-events and violent experiences are associated to mental health, and, second, whether good social relationships with parents, siblings and peers can buffer mental health from stress and violence. The participants were 415 Ghanaian students (aged 14-17 years, M = 16.51; 71% girls). They indicated mental health by depressive symptoms and psychological distress and reported the quality of parental (support and control), sibling (warmth and rivalry) and peer relationships, and exposure to stressful life-events and violence. Hierarchical linear regression models with main and interaction effects were used to analyze the data. Only stressful life-events, but not violence, were associated with higher levels of depressive and psychological distress symptoms. Positive sibling relationships played a buffering mental health role, as stressful life-events were not related with increased depressive symptoms among adolescents enjoying warm and intimate siblingships. No protective function was found for parental or peer relationships, although good maternal and peer relationships were associated with lower levels of depressive symptoms in general.